Literary Citizenship in Scandinavia in the Long Eighteenth Century - Hemstad, Ruth; Kaasa, Janicke S.; Krefting, Ellen; Nøding, Aina (Knowledge and Communication in the Enlightenment World, 2023)
Sheds new light on European and regional book markets, the development of a public sphere and the impact of new media on intellectual, social, religious and political change. How do you become a citizen? Ever since printing was introduced, being a member of society increasingly involved reading and writing: for sociability and belonging, instruction and entertainment, profit and charity, spiritual awakening and political debate. Literary practices shaped and changed identities and the organisation of society during the Long Eighteenth Century. In Scandinavia, this happened locally, as well as transnationally - reading, writing and producing texts involved entanglements within and beyond the borders of the Northern European periphery of Norway, Denmark and Sweden. Focusing on 'literary citizenship', this volume uncovers the different ways in which engagements with print have mediated and established networks and communities, identities and agencies of multiple sorts in an interconnected media landscape. The result is a complex and intriguing history of the book in the Scandinavian region. This history is, on the one hand, influenced by a European market and tradition. On the other hand, it offers an important and different case of regional and local adaptation, marked by what has been termed a 'Northern Enlightenment'. This book will be of interest to scholars of European enlightenment studies and to those who are interested in the continuing debates surrounding print culture and history. This book is available in digital format as Open Access under the Creative Commons license CC-BY-NC. This book and the research upon which it is based was supported by funds from The Research Council of Norway and the National Library of Norway. CONTRIBUTORS: Jens Bjerring-Hansen, Jon Haarberg, Ruth Hemstad, Thor Inge Rørvik, Ellen Krefting, Karin Kukkonen, Ulrik Langen, Aina Nøding, Jonas Nordin, James Raven, Janicke S. Kaasa, Karen Skovgaard-Petersen, Frederik Stjernfelt, Iver Tangen Stensrud and Jonas Thorup Thomsen.